Unveiling Social Networks: Exploring Campus Life at Public Sector Universities in Pakistan - Saeed, Maryam (Pakistan Languages and Humanities Review, 2025)
This study investigates the social networks of students in the public universities of the Federal Capital of Pakistan. Social networks provide students with a set of resources as well as support that is important to students' development, both academically and personally. In the case of universities in Pakistan, little is known about how these networks are formed, maintained, and what the significance of these networks may be for students. We know social networks can facilitate students' intellectual and emotional well-being; the lack of knowledge about social networks is a significant issue. The study uses a qualitative method. Undergraduate students were interviewed to successfully gain in-depth understandings of how social networks operate or develop along with the factors that are affecting them. The purpose of the study was to look at how students develop and manage their social networks, the significance of their social networks for their academic and personal lives, and the role of campus space and policy within the development of social networks. The findings of this study are based on interviews and provide a comprehensive view of the social networks of students at public colleges in Pakistan's Federal Capital. These findings underscore critical factors influencing social network development and maintenance as well as their respective contribution to the students' personal and professional growth.